LEVERAGING DATA ANALYTICS FOR STRATEGIC DECISION-MAKING IN PROFESSIONAL SPORTS ORGANIZATIONS - Abbas, Rawaa Abdulameer (Universitas Negeri Jakarta, 2026)
Background. The integration of data analytics has revolutionized decision-making in professional sports, enhancing operational efficiency, tactical strategies, and financial performance. As teams increasingly rely on big data, analytics has become a crucial tool for optimizing player performance, improving fan engagement, and maximizing revenue. Objectives. This study examines the impact of data analytics on professional sports organizations, focusing on performance optimization, recruitment strategies, and financial sustainability. Method. A mixed-methods approach was employed, combining quantitative analysis (player statistics, match outcomes, revenue metrics) with qualitative insights (expert interviews, fan sentiment analysis). Data from professional sports organizations, coaches, players, and fans were analyzed using statistical models, machine learning, and natural language processing. Results. Findings indicate that analytics-driven performance evaluation enhances coaching decisions, injury prevention, and player recruitment. Fan engagement strategies based on data-driven marketing increase loyalty, while financial analytics improve sponsorship deals and revenue generation. Larger organizations benefit from AI-powered predictive modeling, whereas smaller clubs should adopt cost-effective solutions to enhance competitiveness. Conclusion. Data analytics is a key driver of success in professional sports, enabling smarter decision-making, improved fan engagement, and sustainable financial growth. Investment in advanced technologies and cross-sector collaboration will further enhance competitive advantages in an increasingly data-driven industry.